Coincidence of maps on torus fibre bundles over the circle - Vieira, João Peres [UNESP] (Uniwersytet Mikolaja Kopernika/Nicolaus Copernicus University, 2015)
The main purpose of this work is to study coincidences of fibre- preserving self-maps over the circle S1 for spaces which are fibre bundles over S1 and the fibre is the torus T. We classify all pairs of self-maps over S1 which can be deformed fibrewise to a pair of coincidence free maps.
Keywords: Coincidence; Fibre bundle; Fibrewise homotopy